The impact of treadle pump irrigation technology adoption on poverty in Ghana - Adeoti, A.I.; Barry, Boubacar; Namara, Regassa E.; Kamara, A. (2009)
Treadle pump (TP) technology has been promoted by Enterprise Works in West Africa as an alternative to the traditional rope and bucket irrigation. The aim is to improve output and incomes and reduce poverty among farm households. This paper reports a short term (two years) assessment of the dynamics of its adoption and impacts, with a special focus on poverty reduction. Data used were from primary surveys of adopters and non-adopters of treadle pumps in two regions of Ghana. The data were analyzed using descriptive statistics, budgetary and production function analysis. The results of the study reveal that time and labor savings for irrigation were the major attractive features of the treadle pump for those who adopted it. The difference in net income between adopters and non-adopters was about US$393 per hectare, with an increase in land and labor productivities. About 21% stopped the use of the treadle pump because it broke down, while about 10% shifted to motorized pumping. The study shows that adoption of treadle pumps reduces poverty. It is recommended that increased collaboration with local institutions, such as extension services, will improve the transfer of treadle pump technology to farmers. After-sales service and training of farmers on repairs could reduce treadle pump abandonment. This paper is original as it compares the factors that affect adoption and non-adoption of treadle pumps. It also reveals reasons for abandonment. A multivariate analysis was used to examine the productivity impact of adoption.